Effects of harvesting time on composition of black soldier fly larvae and its optimum inclusion level on growth of spring chickens (tiada security di pdf) - Jibia, Dahiru Soli (2017)
There is high demand for alternative protein source of animal origin for food and feed, which can sustainably be utilized to meet the growing human population need for food and animals’ feed in the near future. Black soldier fly larvae meal was used in this study to substitute the conventional protein ingredient for broiler chicken. The continuous need for a qualitative protein source of animal origin has presented serious struggle for animals and humans. The current study uses black soldier fly larvae for its significant contribution to poultry feed. The bsf larva was established to contain 40% - 60% DM crude protein and metabolizable energy (ME/kcal) that was superior to fishmeal and having a higher amino acid profile than the soybean meal, but equal to the fish meal. Therefore, the study is determined to evaluate the appropriate harvesting age in black soldier fly larva for high nutrient composition and its optimum inclusion level for the performance of young commercial broiler chicks. The set media for larvae harvest were arranged on the same day and harvested according to target age 6 d, 12 d, 18 d and 24 d. Larvae analysis was carried out for percent crude protein, crude fat, ash, dry matter, organic matter and moisture content. Result showed significant difference (P < 0.05) among the treatments with T3 18 d was highly significant 50.47% CP against 6 d, 12 d and 24 d approximately T1 32%, T3 34%, and T4 37% respectively. Amino acid profile was significant (P < 0.05) apart from Aspartic acid, glycine, proline and lysine (P>0.05). Ninety six day old commercial broiler chick were arranged into four treatment groups, subdivided into four replicates each replicate allotted to six chicks 4 X 4 X 6 (T1 – T4) in a completely randomized design using SAS 9.4 software model, means comparison was carried out by Duncan multiple range test. Four inclusion levels of black soldier fly larvae (bsfl) experimental diets were allocated to each treatment group (0%, 5%, 7.5% & 10%), record of performance were analyzed: where feed intake, body weight gain, daily weight gain, feed conversion ratio and mortality were significantly higher (P< 0.001) except the final body weight (P>0.05). Sensory and meat characteristics parameters; odor, taste, color (L* a* b*), shear force and cooking loss were not significant (P>0.05), however, meat color, tenderness and pH (P<0.05). Carcass characteristics and blood parameter analyzed showed (P<0.001) in thigh muscle, liver and (P<0.05) in urea only. While the remaining parameters: carcass weight, dressing percentage, breast muscle, drumstick, wings, cholesterol and total blood protein (TBP) were found to be no significant (P > 0.05) in all the treatments. Conclusively, the study revealed that larvae should best be harvested on 18th d and 5% dietary Hermetia inclusion level was the optimum for young commercial broiler chicks.